The Influence of Nursing Service Quality on Word-of-Mouth Communication among Inpatients at X Hospital Bandar Lampung in 2023 - Putu Tira Septiyanigiri, Ni; Leo Bunga, Asnet; Priyo Hastono, Sutanto (Al Makki Publisher, 2024)
The nursing service is essential to hospital patient recovery. It also shows the hospital's healthcare performance. This study examines how nursing quality affects word-of-mouth communication among RS X Bandar Lampung hospitalized patients in 2023. A true Experimental Design with a posttest-only control group was adopted. The sample included 80 people, divided equally into 40 intervention and 40 control groups. The control and intervention groups showed significant differences in service quality, including empathy, tangibility, assurance, reliability, and responsiveness (p-value = 0.000 < 0.05). Significant differences in word-of-mouth communication were seen between the control and intervention groups (p-value = 0.000 < 0.05). The simple linear regression test significantly impacted empathic nursing service quality (p-value < 0.05). The quality of tangible nursing services was also affected (p-value < 0.05). The quality of nurse service assurance also had an impact (p-value < 0.05). Nurse attentiveness impacted word-of-mouth communication in control and intervention group patients (p < 0.000 < 0.05). Nursed service reliability impacted word-of-mouth communication in treatment and control groups (p-value = 0.004 < 0.085). The management of X Hospital Bandar Lampung must constantly teach nurses about nursing service quality. They should also assess training success by measuring nurse service quality with patient surveys and questionnaires.